2016
DOI: 10.1155/2016/7230450
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Variability and Trend Analysis of Annual Rainfall in North Africa

Abstract: The IPCC climate models predict, for the Maghreb countries, lower rainfall and increased aridity. Current observations in the three countries of central Maghreb (Morocco, Algeria, and Tunisia) are not consistent with these predictions. To demonstrate this new trend, a detailed regional analysis of rainfall evolution is conducted. This investigation is based on the calculation of the reduced centered index and the chronological graphical method of processing information (MGCTI) of “Bertin matrix” type. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 23 publications
5
26
0
1
Order By: Relevance
“…As to what concerns the Mediterranean area, these findings agree with the results of other researchers, who evidenced a clear tendency towards drier conditions of the eastern Mediterranean and negative trends, thus not always significant, in the total rainfall amounts in the western and The results of the present study also confirm past local studies on Europe and Africa, which highlighted relatively large positive trends in the Northern Hemisphere mid-latitudes and high latitudes and a negative one in the subtropics (e.g. New et al 2001;Nouaceur & Mur arescu 2016;Deitch et al 2017). These results also agree with other local studies in the Mediterranean region which evidenced a reduction in precipitation and an increase in the mean and largest dry periods (Nastos & Zerefos 2009;Cindrić et al 2010;S anchez et al 2011;Liuzzo et al 2016;Montaldo & Sarigu 2017).…”
Section: Discussionsupporting
confidence: 93%
“…As to what concerns the Mediterranean area, these findings agree with the results of other researchers, who evidenced a clear tendency towards drier conditions of the eastern Mediterranean and negative trends, thus not always significant, in the total rainfall amounts in the western and The results of the present study also confirm past local studies on Europe and Africa, which highlighted relatively large positive trends in the Northern Hemisphere mid-latitudes and high latitudes and a negative one in the subtropics (e.g. New et al 2001;Nouaceur & Mur arescu 2016;Deitch et al 2017). These results also agree with other local studies in the Mediterranean region which evidenced a reduction in precipitation and an increase in the mean and largest dry periods (Nastos & Zerefos 2009;Cindrić et al 2010;S anchez et al 2011;Liuzzo et al 2016;Montaldo & Sarigu 2017).…”
Section: Discussionsupporting
confidence: 93%
“…In Africa, a gradual return to wetter conditions is observed in Sahelian and Soudanian areas since the 1990s [2]. The same situation is reported since early 2000s across Algeria and Tunisia and from 2008 in Morocco by Nouaceur et al [3]. There are contrasting trends throughout seasonal variations of rainfall.…”
Section: Introductionsupporting
confidence: 55%
“…Along with the decrease in rainfall during the wet season, wintertime drying has been observed over large parts of western North Africa at least since the 1970s (Hertig and Tramblay 2017;Tramblay et al 2013a;Zittis 2018). However, some wet years observed since the 2000s can be attributed to increased climate variability (Donat et al 2013;Nouaceur and Murărescu 2016). With respect to heavy rainfall events, most parts of North Africa show no significant trends over the last decades (Nashwan et al 2019;Nasri et al 2016;Tramblay et al 2012), while a general increase in drought frequency can be observed in all countries (see Hertig and Tramblay 2017 and Table 1).…”
Section: Exposure To Climate Changementioning
confidence: 99%